Cyclohexylation of resorcinol with cyclohexanol catalyzed by tungstophosphoric acid supported zirconia catalysts - Balasubramanian, V. V.; Devassay, B. M.; Halligudi, S. B.; Deepika, R.; Umbarakar, S. B.; Vinu, A. (Journal of Nanoscience and Nanotechnology, 2018)
We demonstrate a highly active and reusable heterogeneous catalyst system, tungstophosphoric acid (TPA) supported on zirconia (ZrO2), for the cyclohexylation of resorcinol by cyclohexanol to produce value added chemicals such as 2-cyclohexyl resorcinol, 4-cyclohexyl resorcinol and 3-Hydroxy cyclohexyl phenyl ether under liquid phase reaction condition. TPA/ZrO2 catalysts prepared with different TPA loadings (5-30 wt.%) by wet impregnation method and calcined in the temperature range of 650-850 degrees C were characterized by Nitrogen sorption analysis, XRD, FTIR, DTG and DTA, and P-31 MAS NMR spectroscopy. Among the catalysts studied, 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C gave the highest conversion of resorcinol (51.2%) with the selectivities for 3-Hydroxy cyclohexyl phenyl ether (53.9%) and 2-cyclohexyl resorcinol and 4-cyclohexyl resorcinol together (46.1%) under optimum reaction conditions. However, the selectivity of the products were controlled by varying the reaction conditions. At higher conversion of resorcinol (78.9%), only C-alkylated products were formed at 200 degrees C with 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C. The combination of TPA and ZrO2 coupled with calcination temperature offered an excellent platform for the conversion of resorcinol into O- or C-alkylated products.
Keywords: 15% TPA/ZrO2; Cyclohexanol; Cyclohexylation; Keggin TPA; Resorcinol